2004
DOI: 10.1103/physrevlett.92.194501
|View full text |Cite
|
Sign up to set email alerts
|

Nanoflares and MHD Turbulence in Coronal Loops: A Hybrid Shell Model

Abstract: A model to describe injection, due to footpoint motions, storage, and dissipation of MHD turbulence in coronal loops, is presented. The model is based on the use of the shell technique in the wave vector space applied to the set of reduced MHD equations. Numerical simulation showed that the energy injected is efficiently stored in the loop where a significant level of magnetic and velocity fluctuations is obtained. Nonlinear interactions among these fluctuations give rise to an energy cascade towards smaller s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
87
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(92 citation statements)
references
References 19 publications
4
87
1
Order By: Relevance
“…According to this scenario, multiscale dissipation events in the corona result from turbulent intermittency (inhomogeneous energy dissipation) associated with a cross-scale energy cascade (Boffetta et al 1999;Nigro et al 2004). The energy is initially injected at the largest scale is due to, e.g., photospheric motions.…”
Section: Routes To Multiscale Dissipationmentioning
confidence: 99%
See 2 more Smart Citations
“…According to this scenario, multiscale dissipation events in the corona result from turbulent intermittency (inhomogeneous energy dissipation) associated with a cross-scale energy cascade (Boffetta et al 1999;Nigro et al 2004). The energy is initially injected at the largest scale is due to, e.g., photospheric motions.…”
Section: Routes To Multiscale Dissipationmentioning
confidence: 99%
“…Among the most important such processes are the injection of helicity associated with new magnetic structures (Falconer et al 2008;Abramenko & Yurchyshyn 2010;McAteer et al 2010;Conlon et al 2010) as well as the fragmentation of the existing magnetic flux subject to magnetic footpoint shuffling due to the turbulent photospheric convection (Lamb et al 2008;Chaouche et al 2011;Abramenko 2005). The amount of free coronal magnetic energy supplied through these processes is in a quasi-steady balance with the energy released via coronal heating and flaring activity (Simon et al 2001), possibly mediated by coronal loop turbulence and waves (Davila 1987;Ofman et al 1998;Nigro et al 2004;Buchlin et al 2005;De Pontieu et al 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are dynamical models of the nonlinear interactions between fields on different scales and have been developed for the study of turbulence in various frameworks such as hydrodynamics (Gledzer 1973), MHD (Gloaguen et al 1985;Yamada & Ohkitani 1987), reduced MHD (Nigro et al 2004;Buchlin & Velli 2007), Hall-MHD (Galtier & Buchlin 2007), and MHD with a global rotation rate (Perrone et al 2011). A review of shell models can be found in Biferale (2003) and in the book by Bohr et al (2005).…”
Section: Introductionmentioning
confidence: 99%
“…In this model, shell-models of 2D MHD are coupled by Alfvén waves travelling along B 0 , and energy is only input by movements of the photospheric footpoints of the loop. This geometric setup is the same as the one used for the cellular automaton described by Buchlin et al (2003), and it gives a model similar to the one described by Nigro et al (2004). Here we use an independent implementation of these ideas to obtain the time series 3 .…”
Section: Coupled Shell-modelsmentioning
confidence: 99%